The Vector Error Correction Model Analysis on The Dow Jones Islamic Market Index of Malaysia, Japan, China and The Jakarta Islamic Index - Ali, Andi Nurhidayati; Syariati, Alim; Rusnawati, Rusnawati (Journal of International Conference Proceedings, 2024)
The development of the Islamic capital market in Indonesia cannot be separated from the influence of foreign capital markets, especially in the Asian region. Fluctuations occuring in the JII indicate the existence of a contagious effect caused by stock price movements in a country that can affect stock price movements in other countries or sectors. This study aims to determine the relationship between DJIMI Malaysia, Japan, China and the JII. This research uses the Vector Error Correction Model (VECM) method using monthly data on the stock price index from January 2021 to December 2023. The results showed that in the long term, DJIJP has a positive significant relationship with the JII, DJICHK has a negative significant relationship with the JII, while DJIMY has no statistically significant relationship with the JII. While in the short term DJIMY, DJIJP and DJICHK do not have a significant relationship with the JII. This research provides information for investors and academics in understanding the dynamics of Islamic stock markets in Malaysia, Japan, China and Indonesia.